THE INFLUENCE OF SOCIAL SUPPORT ON CAREER ADAPTABILITY IN FRESH GRADUATE IN PADANG CITY - Ragil Azira Suhendra; RIZAL KURNIAWAN (Causalita, 2024)
This research aims to find out whether there is an influence of social support on career adaptability in fresh graduates in Padang City. Career adaptability itself is a person's readiness to complete predictable tasks and participate in work roles, as well as being able to master unexpected situations that may occur due to changes in work and working conditions. This research received 230 fresh graduate respondents, including 125 female respondents and 105 male respondents. The technique used to collect subjects was purposive sampling. This research uses a quantitative method where data is collected through distributing questionnaires. Data was collected from two scales, namely the career adaptability scale which consists of 22 items with a reliability coefficient of 0.847 and the social support scale which consists of 12 items with a reliability coefficient of 0.835. Data analysis was carried out using simple linear regression techniques. Based on data analysis using simple linear regression techniques, it was found that the correlation value was r = 847. From the output, the coefficient of determination (R Squere) was 0.717, the calculated F value was 578.824 with a significance level of 0.000 < 0.05. It can be concluded that social support has a positive influence. positive and significant impact on career adaptability of fresh graduates in Padang City.